Karakteristik pasien retinoblastoma di RSUP Sanglah pada bulan April 2015 – Desember 2017 - Monika Nur Indah Pawana; Ni Putu Ekawati; Luh Putu Iin Indrayani Maker (Intisari Sains Medis, 2019)
Background: Retinoblastoma is one of the intraocular tumors originate from the lining of the retinal eye layer component. This disease is more common in children. Retinoblastoma incidence rate tend to be constant every year, but epidemiological data about retinoblastoma in Indonesia not yet available.Aim: this study aims to determine the characteristics of patients with retinoblastoma at RSUP Sanglah Denpasar from April 2015 till December 2017.Method: The study was a descriptive cross sectional design which was conducted at RSUP Sanglah Denpasar. Data obtained was in the form patient’s medical records registered between April 2015 – December 2017.Results: Of the 22 patients, the age average was 5.06 ± 3.06 years with the highest gender proportion was male (55%). Leukokoria (68%) was the main complaint. Most sites were unilateral (59%). Staging for unilateral was Group D (47%) and for bilateral was OD Group D, OS Group E (25%) and OD Grup E OS Grup C (25%) There were two patients had family history of retinoblastoma (18%). Histopathological finding showed only 4.54% with typical appearance of Flexner Wintersteiner Rossete, 36% of patients showed pseudorossete, and the remains classified as undifferentiated type. Almost half of the patients have a tumor invation, and most of them have necrosis in their tumor. The most common management for retinoblastoma is chemotherapy (52%) followed by enucleation (48%). Conclusion: There’re variety in characteristics of retinoblastoma. Further research needed to know the characteristic of retinoblastoma significantly.